2018
DOI: 10.1097/01.naj.0000549685.59006.ad
|View full text |Cite
|
Sign up to set email alerts
|

Infant Safe Sleep Practices in the United States

Abstract: Risk of sleep-related infant deaths can be reduced by improving safe sleep practices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 7 publications
2
5
0
Order By: Relevance
“…Sleep-related infant deaths, from sudden infant death syndrome (SIDS), accidental suffocation or strangulation in bed, and other unknown causes started to decline in the 1990s in response to an increase in guidelines and education on safe infant sleep practices (Bombard et al, 2018b; Colson et al, 2009). However, sleep-related deaths still account for approximately 3400 infant deaths in the United States (Centers for Disease Control and Prevention, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sleep-related infant deaths, from sudden infant death syndrome (SIDS), accidental suffocation or strangulation in bed, and other unknown causes started to decline in the 1990s in response to an increase in guidelines and education on safe infant sleep practices (Bombard et al, 2018b; Colson et al, 2009). However, sleep-related deaths still account for approximately 3400 infant deaths in the United States (Centers for Disease Control and Prevention, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…According to the Centers for Disease Control and Prevention Pregnancy Risk Assessment Monitoring System (PRAMS), racial and ethnic minority populations are less likely to follow all recommended safe infant sleep guidelines (Bombard et al, 2018a). For example, African American caregivers are less likely (38%) to place their infant to sleep on the back, while American Indians or Alaskan Natives are more likely to practice bed-sharing (84%), and Asians or Pacific Islanders are more likely to use soft bedding (55%) (Bombard et al, 2018a). Teenage mothers (<20 years) have been found least likely to adhere to the AAP guidelines compared to mothers over 30 years of age (Caraballo et al, 2016; Hirai et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Third, bed-sharing appears to be influenced by sociodemographic factors. In early childhood, it has been reported that US bed-sharing rates are higher in Black, Hispanic, and mixed race families than White families [ 5 8 , 10 ]. Beyond infancy, very little is known about US bed-sharing rates in families across different n racial and ethnic groups, particularly among those of Asian, American Indian or mixed race backgrounds.…”
mentioning
confidence: 99%
“…Beyond infancy, very little is known about US bed-sharing rates in families across different n racial and ethnic groups, particularly among those of Asian, American Indian or mixed race backgrounds. Additionally, there are reports that bed-sharing is more commonly practiced among families with lower socioeconomic status and parental education, and in families with a single mother as head of household [ 4 6 , 10 , 11 ]. These results were found more consistently in large, representative US samples [ 4 , 10 ] than in smaller, predominantly low income [ 8 ], urban [ 5 ] and Hispanic [ 7 ] samples.…”
mentioning
confidence: 99%
See 1 more Smart Citation